Solubilidade de equações polinomiais - Vieira, Gleyca Farias (2021)
This master thesis presents the solution set of polynomial equations, as well as the necessary conditions for it to exist in a given algebraic structure. The solubility of a polynomial equation by radicals was extensively studied by Evariste Galois. We will approach, from ´ group theory, the possibilities of the roots of a n degree polynomial to be given from its coefficients.